Assignment of Credit and Blame for Performance Outcomes - Crant, J. Michael; Bateman, Thomas S. (Academy of Management Journal, 1993)
Assigning credit and blame to others for their successful and unsuccessful performances is a ubiquitous, yet relatively unstudied, process in organizations. Using a sample of 120 accountants, we assessed three predictors of the assignment of credit and blame—self-handicapping, type of causal account, and performance outcome—and two consequences of such assignment: reward allocation and impressions of an actor. Use of self-handicapping and external causal accounts diminished observers' assignments of blame for failure. In contrast, self-handicapping and causal accounts did not influence assignment of credit for success. Assignment of credit and blame significantly predicted reward allocation and impressions of the actor. We discuss implications for theory and practice and directions for future research.